Settlement Of Cases Of Criminal Acts Of Violence Against Women And Children In The Jurisdiction Of Batanghari Regency Which Are Handled Through The Resort Police - Islah, Islah (International Journal of Multidisciplinary Sciences and Arts, 2024)
The aim of this research is to find out how violence against children and women can happen to anyone and the perpetrators are not only people the child has just known, people the child has known for a long time can also be the perpetrators of violence against the child, even family or school friends and the child's playmates. can be the perpetrator. The research method used is an empirical juridical approach, namely a type of legal research focused on facts in the field found in this type of research, the Socio Criminological approach. All information is through direct observation and interviews with the research object. The research results showed that the increasing prevalence of acts of violence against children shows that children are often used as objects of violence because they are physically and mentally immature. Criminal acts of violence against children cause children to experience prolonged trauma and often make victims remain silent, therefore physically, mentally, sexually and the child's approach must receive special attention. The conclusion is that the problem of crime victims has not been an old thing for a long time, simply because violence has received less attention, perhaps it has been forgotten.